Mundo-vida travesti: abordagem fenomenológica das travestilidades - Davi, Edmar Henrique Dairell; De Toledo Bruns, Maria Alves [UNESP] (Associacao Brasileira de Psicologia, 2015)
The objective of the present article is the understanding of the meanings and senses that three transvestites attribute to their experiences as sex professionals. We derive from the premise that transvestites, being excluded from their families and from the formal job market, find in the prostitution activity a natural' course, their fate, or refuge given the prejudice against such individuals who break way from gender patterns. However, the questioning of such phenomenon led us to observing that besides guaranteeing the transvestites' a living, the sex market influences the construction of transvestility in various ways. From that perspective, we carry out our analysis supported by the phenomenological method and ideas of philosopher Maurice Merleau-Ponty in order to understand the life experience of these three Class D transvestites aged between 24 and 42. Our comprehensive analysis pointed out three categories: The street, where the construction of the being-transvestite takes place; Displacement, which deals with process of resignifying the being-transvestite when they move and occupy spaces that are beyond their prostitution practice; and Perspectives, category in which the transvestites reveal their dreams and life projects. These categories help us to understand the life experience in prostitution as an experience that enables not only their subsistence but also the elaboration of the specificities expressed through the language, corporality, and other elements that comprise the transvestite life-world.
Transvestite life-world: A phenomenological approach to transvestility
Keywords: Merleau-Ponty; Phenomenology; Prostitution; Transvestites